Infrared phonons as a probe of spin-liquid states in herbertsmithite ZnCu3(OH)6Cl2. (23rd January 2017) - Sushkov, A B; Jenkins, G S; Han, Tian-Heng; Lee, Young S; Drew, H D
Abstract: We report on temperature dependence of the infrared reflectivity spectra of a single crystalline herbertsmithite in two polarizations—parallel and perpendicular to the kagome plane of Cu atoms. We observe anomalous broadening of the low frequency phonons possibly caused by fluctuations in the exotic dynamical magnetic order of the spin liquid.